Experimental measurements, thermodynamic modeling and molecular dynamics simulation of the multiphase equilibria of {1-butanol + n-butyl acetate + [EMIM][EtSO4]} systems at 101.3 kPa - Freire, Nian V. [UNESP]; Biswas, Rima; Arce, Pedro F. (Elsevier, 2025)
Ionic liquids (ILs) are organic salts with normal melting temperatures lower than 373 K and have interesting properties to be used as environment-friendly solvents, as low volatility, high thermal stability, and easy containing and recycling ability. Besides, they are versatile molecules whose anions and cations can be changed to solubilize different organic compounds. For these reasons, ionic liquids can be used in many industrial applications, such as in separation processes as azeotropic distillation and liquid–liquid extraction, and, because of that, it is important to know the phase equilibrium behavior for equipment design for these processes. However, experimental data for systems containing ionic liquids are very scarce. This work aimed to analyze the fluid phase behavior of the 1-butanol + n-butyl acetate + [EMIM][EtSO4] system in liquid–liquid (LLE), vapor–liquid (VLE) and vapor–liquid–liquid equilibria (VLLE) at 101.3 kPa. LLE was analyzed in glass-jacketed vessels and VLE and VLLE were analyzed in a modified Othmer ebuliometer. Compositions of each phase sample were obtained from calibration curves with built-in functions of the refractive index and density. Experimental data were submitted to thermodynamic consistency tests and the consistent points were modeled with the Group Contribution Volume Translated Peng-Robinson (GC-VT-PR) and Non-Random Two-Liquid (NRTL) models. Vapor pressure and saturated liquid density data for the ionic liquid, necessary for the determination of the pure component parameters, were obtained from analytical methods. For the LLE, a phase stability test was also done to evaluate the data consistency by the Gibbs energy of the mixing surface and to determine the plait point. Molecular dynamics (MD) simulations, performed by NAMD software, were also conducted to understand the behavior of the multiphase fluid equilibria, by analyzing the structural properties of the components. Results of the thermodynamic modeling in terms of the deviations of temperature and mole fractions showed that these models were adequate to study the phase behavior of systems containing ionic liquids, while the dynamic simulations suggested that the ionic liquid molecules strongly interact with 1-butanol molecules when compared with the n-butyl acetate molecules.
Keywords: Experimental measurements; Ionic liquid; Molecular dynamics simulations; Multiphase equilibria; Thermodynamic modeling